2016
DOI: 10.1152/ajpendo.00412.2015
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral, but not central, GLP-1 receptor signaling is required for improvement in glucose tolerance after Roux-en-Y gastric bypass in mice

Abstract: Carmody JS, Muñoz R, Yin H, Kaplan LM. Peripheral, but not central, GLP-1 receptor signaling is required for improvement in glucose tolerance after Roux-en-Y gastric bypass in mice. Am J Physiol Endocrinol Metab 310: E855-E861, 2016. First published March 29, 2016; doi:10.1152/ajpendo.00412.2015.-Roux-en-Y gastric bypass (RYGB) causes profound weight loss and remission of diabetes by influencing metabolic physiology, yet the mechanisms behind these clinical improvements remain undefined. After RYGB, levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Unchanged GLP-1R expression in colonic mucosa agrees with our previous work as well as others showing GLP-1R is not required for the beneficial effects of RYGB [ 39 , 40 ]. However, GLP-1 acting on GLP-1R expressed on pancreatic β-cells is required for partial improvement of glucose tolerance after RYGB in mice [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unchanged GLP-1R expression in colonic mucosa agrees with our previous work as well as others showing GLP-1R is not required for the beneficial effects of RYGB [ 39 , 40 ]. However, GLP-1 acting on GLP-1R expressed on pancreatic β-cells is required for partial improvement of glucose tolerance after RYGB in mice [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that obese mice do not increase food intake in response to a GLP‐1 antagonist, extendin‐9, suggesting a degree of insensitivity to the anorexigenic effect of GLP‐1 in obesity. Interestingly, other effects of GLP‐1 such as regulation of blood glucose levels appear to be maintained . However, the GLP‐1 analog liragluteride in addition to improving insulin sensitivity also leads to weight loss in humans .…”
Section: Small Intestinal Vagal Modulation In Health and Obesitymentioning
confidence: 99%
“…Interestingly, other effects of GLP-1 such as regulation of blood glucose levels appear to be maintained. 123 However, the GLP-1 analog liragluteride in addition to improving insulin sensitivity also leads to weight loss in humans. 124 Administration of the GLP-1 agonist exendin-4 has been shown to reduce food intake in obese DIO-P rats, but by a smaller amount than DIO-R rats.…”
Section: Glucagon Like Peptidementioning
confidence: 99%
“…On the other hand, meal termination and satiety are mediated by secretion of anorectic gut hormones such as glucagon‐like peptide (GLP) 1, which are secreted by enteroendocrine cells of the small and large intestine following direct interaction of ingested nutrients with taste and fatty acid receptors on their luminal surfaces. Importantly, GLP‐1 and other gut peptides also serve to enhance postprandial nutrient utilization, through both stimulation of insulin secretion and increased peripheral insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%